Advantages of a Free Software Culture for Qualitative Researchers in the Social Sciences - Ernesto Israel Santillan-Anguiano; Emilia Cristina González-Machado (International Journal of Qualitative Research, 2023)
This paper aims to show the characteristics of free software and its implications for qualitative analysis in social research, especially in the case of new researchers and researchers with limited financial resources, as happens in third-world countries. First, the elements of qualitative research are described and understood as an approach linked to the interpretation and meanings that are given to the world. Secondly, the functions and handling of the RQDA software are explained. The main feature of RQDA is the fact that it is a free and open-source cross-platform tool, which allows project administration for data management purposes. The results show that even with the limitations that this type of tool may have, they offer a series of advantages that make their use possible and desirable to develop quality social research. Regarding the conclusions section, a reflection is offered on the use of technology based on free software for social research purposes, which must consider the pros and cons during its implementation. Concepts such as that of open access, or free culture, incorporate various forms of attending to historical problems suffered by science and education.